Dust - Cornwell, Patricia Daniels (New York : G. P. Putnam's Sons, 2013)
The body of a young woman has been discovered on the Massachusetts Institute of Technology's rugby field and physical evidence links the case to a series of uniquely weird homicides in Washington, D.C., where Scarpetta's FBI husband has been deployed to help capture a serial killer dubbed the Capital Murderer.
Keywords: Scarpetta, Kay (Fictitious character) -- Fiction; Medical examiners (Law) -- Fiction; Forensic pathologists -- Fiction; Murder victims -- Massachusetts -- Cambridge -- Fiction; Serial murders -- Washington (D.C.) -- Fiction; Cambridge (Mass.) -- Fiction; Washington (D.C.) -- Fiction; Mystery fiction; Suspense fiction